MANAJEMEN PENDEKATAN FISIOTERAPI DENGAN TERAPI LATIHAN DAN POSTURAL CORRECTION TERHADAP NYERI MUSKULOSKELETAL LOW BACK PAIN SELAMA KEHAMILAN - Ismaningsih Ismaningsih; Nurmaliza Nurmaliza; Siti Muawanah (LPPM Universitas Abdurrab, 2024)
Low back pain (LBP) is a common musculoskeletal problem during pregnancy with an estimated prevalence of 30% -78% of pregnant women experiencing complaints in the form of low back pain at some point in their pregnancy. This type of LBP can occur in the pelvic bones between the posterior iliac crest, gluteal folds or in the lumbar spine area. In this case the pain usually spreads to the buttocks, legs and feet. This is due to hormonal changes, blood circulation and biomechanical changes. low back pain usually increases with increasing gestational age, interfering with work, every activity and sleep so that it has an impact on the quality of life of pregnant women. This research aims to determine the effect of providing exercise and postural correction on the condition of low back pain during pregnancy. Method: this research uses quasie experimental with a pre and post test research design without control group design, the population in this study were all pregnant women who were experiencing low back pain who received physiotherapy services in the form of providing exercise and postural correction totaling 15 clients. Results: based on paired sample tests in the group treatment obtained a value of P = 0.001 (P<0.05) with a mean value of 5.27 ± 2.07, meaning that there were significant differences in results before and after the intervention of providing exercise and postural correction. Conclusion: there was a decrease in the VDS (verbal descriptive scale) value in low back pain conditions by providing exercise and postural correction interventions. This can be seen from the difference between the results before and after the intervention, which means that the exercise and postural correction interventions significantly have a very good effect in reducing pain scores in low back pain conditions during pregnancy